Tawhid Concepts and Its Learning According to Ibn Taimiyah - Din Muhammad Zakariya (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2019)
The purpose of this study is to explore the tawhid concept and its learning according to Ibn Taymiyyah. This research is a qualitative research with literature research type, and the data analysis technique uses inductive and deductive. The findings of this study can be concluded: first, according to Ibn Taimiyah Tawhid is insisting on Allah in matters that are specific to God, both in rububiyah, uluhiyah and asma’ and shifat. Second, the relationship between the three types of tawẖîd is in the correlative and comprehensive form. Therefore, tawẖîd rububiyah is a necessity of tawẖîd uluhiyah, while tawẖîd rububiyah is the preamble of tawẖîd uluhiyah. As for the tawẖîd asma’ and shifat, then also contained in it also the two types of tawẖîd, meaning people who force God with all that he has from al-asma' al-husna and noble qualities that are not possessed except by Him, then by he himself admitted tawẖîd rububiyah and uluhiyah. Keywords: Concept, Tawhid, Ibn Taimiyah